DNA PROFILING - TSAILA, MATINA (Open Schools Journal for Open Science, 2024)
DNA, a complex molecule found in all living organisms, carries vital information for their construction. Inherited from one generation to the next, DNA is present in nearly every cell of multicellular organisms, resembling a double helix structure. DNA profiling, pioneered in 1984 by Dr. Alec Jefferys, is a forensic method used to identify individuals based on their unique DNA profiles. This technique, also known as DNA fingerprinting, analyzes specific sections of DNA to match samples in criminal investigations and paternity tests. Despite its utility, it faces challenges such as sample contamination, improper preparation procedures and misinterpretation of results, leading to discrepancies between biological evidence and its legal implications in court cases.